1990
DOI: 10.1128/aac.34.10.1944
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and dose proportionality of cefmetazole in healthy young and elderly volunteers

Abstract: The pharmacokinetics and dose proportionality of cefmetazole were studied in 24 healthy volunteers (12 young and 12 elderly). Each volunteer received single 0.5-, 1-, and 2-g doses of cefmetazole administered intravenously over 5 min according to a three-way crossover design. Serial plasma and urine samples were collected over a 24-h period following dosing and assayed for cefmetazole by a high-performance liquid chromatography method. Results of the dose proportionality portion of the study indicated that cef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…These findings were considered reasonable because more than 85% of CMZ is excreted as the unchanged compound in the urine, and excretion is mainly renal. A CL CMZ of 7.04 L/h (Ccr : 100 mL/min) and a Vd CMZ of 10.4 ± 1.6 L (Bw : 47.5 to 89.0 kg) were generally consistent with the results of Borin et al (CL : 6.96 L/h, Vd : 11.9 ± 4.2 L) [7] and Wong-Beringer et al (Vd : 0.14 to 0.28 L/kg) [8]. …”
Section: Discussionsupporting
confidence: 87%
“…These findings were considered reasonable because more than 85% of CMZ is excreted as the unchanged compound in the urine, and excretion is mainly renal. A CL CMZ of 7.04 L/h (Ccr : 100 mL/min) and a Vd CMZ of 10.4 ± 1.6 L (Bw : 47.5 to 89.0 kg) were generally consistent with the results of Borin et al (CL : 6.96 L/h, Vd : 11.9 ± 4.2 L) [7] and Wong-Beringer et al (Vd : 0.14 to 0.28 L/kg) [8]. …”
Section: Discussionsupporting
confidence: 87%
“…We investigated the PK parameters of CMZ in dogs based on the results of blood concentration transition after bolus administration. Borin et al ( 25 ) determined the corresponding PK data in young adult humans, ranging in age from 21 to 40 years, when intravenously administered, as follows: the mean residence time (MRT) was 1.78 h, the elimination half-life (T1/2) was 1.34 h, total body clearance (CL) was 0.10 L/h/kg, and the volume of distribution (Vd) was 0.17 L/kg. Our study indicates the shorter MRT and T1/2, higher CL, and larger Vd in dogs administered with CMZ, compared with the PK data in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Cephalosporin dosage regimens and serum half-lives (t'l2) in neonates, children and the elderly. Dosages listed do not reflect those for life-threatening infection or meningitis (data from Andritz et al 1984;Blouin et al 1989;Borin et al 1990;Faulkner et al 1988b;Hayton 1986;LeBel et al 1985;Meyers et al 1987Meyers et al , 1989Sugihara et al 1988 Nilsson-Ehle 1987; Meyers et al 1989;Montamat et al 1989). Pharmacokinetic studies of ceftazidime, ceftizoxime, and cefmenoxime conducted in elderly populations showed a doubling of tl/, by the age of 70, indicating the need for dosage reduction for these renally eliminated cephalosporins in this age group.…”
Section: Effect Of Agementioning
confidence: 96%
“…Reductions in CLR and protein binding often present in this population lead to no apparent change in the t'l2 of ceftriaxone (Hayton & Stoeckel 1986). Dosage adjustment in the elderly is not indicated for cefetamet ), cefmetazole (Borin et al 1990) or cefixime (Faulkner et al 1988b) if the renal function remains normal other than the usual CLCR decline with aging [to CLCR 30 mlfmin (1.8 L/h)].…”
Section: Effect Of Agementioning
confidence: 99%